2008
DOI: 10.1016/j.jtcvs.2008.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Formation of anti–platelet factor 4/heparin antibodies after cardiac surgery: Influence of perioperative platelet activation, the inflammatory response, and histocompatibility leukocyte antigen status

Abstract: Patients with a greater amount of perioperative inflammation could be more likely to have anti-platelet factor 4/heparin antibodies 1 to 2 weeks later. We provide additional evidence that the histocompatibility leukocyte antigen CW4 confers genetic susceptibility in an acquired inflammatory disorder that includes the anti-platelet factor 4/heparin immune response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…This suggests a possible mechanism of B-cell tolerance for PF4/heparin complexes in patients with chronic inflammatory disorders such as RA. A recent study of anti-PF4/ heparin immunization in patients after cardiac surgery suggested that perioperative inflammation affects the immune response [29]. Alternatively, chronic rheumatoid inflammation may downregulate these perioperative inflammations that contribute to occurrence of anti-PF4/ heparin Ab in RA patients.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests a possible mechanism of B-cell tolerance for PF4/heparin complexes in patients with chronic inflammatory disorders such as RA. A recent study of anti-PF4/ heparin immunization in patients after cardiac surgery suggested that perioperative inflammation affects the immune response [29]. Alternatively, chronic rheumatoid inflammation may downregulate these perioperative inflammations that contribute to occurrence of anti-PF4/ heparin Ab in RA patients.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of anti-PF4/heparin immunization in postcardiac surgery patients found evidence that proinflammatory factors support the costimulation of B cells. 38 This might also explain the decrease of antibody titers despite maintaining heparin, as any proinflammatory costimuli will typically decline soon after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Such an association could represent the effects of a common factor, such as the degree of intra-or postoperative inflammation, which could influence both seroconversion frequency as well as venous graft occlusion. In this regard, it is worth noting that one group has reported an association between a marker of inflammation and antibody formation in cardiac surgery patients [19] (however, we did not examine markers of inflammation in our current study). Moreover, Selleng et al [20] found an association between the pre-operative presence of IgM class antibodies and subsequent nonthrombotic morbid events in post-cardiac surgery patients, which they concluded was unlikely to reflect any HIT-related pathomechanism, but which they speculated could represent an independent factor such as inflammation.…”
Section: Discussionmentioning
confidence: 77%